The Utilization of Skipjack Tuna (Katsuwonus pelamis) Availability in Prigi Sustainable Fisheries Management, East Java - Jonathan Graydam Genti; Marsoedi Marsoedi; Aminudin Afandhi (Graduate Program, 2016)
Skipjack tuna is one of the fishery commodities which has high economy value due to the high demand and high prices in the export commodities. The purpose of this research is to identify and analyze the potential resources of tuna and also determine its alternative management in Prigi Fishing Port (Pelabuhan Perikanan Nusantara Prigi). This research was carried out at Prigi Fishing Port, Trenggalek, East Java from February to April 2016. The method used in this research was descriptive method. The data analysis methods were the standardization of the fishing gear, the analysis of catch per unit effort (CPUE), total allowable catch (TAC), and the skipjack tuna fishery management concept at Prigi Fishing Port. The fishing gears which were used to catch skipjack tuna are payang seine, trolling line and purse seine. However, the standard fishing gear used to catch the skipjack tuna was trolling line. CPUE analysis results were obtained from the CPUEstd average value in 2005-2014 as many as 4.79 kg/unit. The allowed amount of the skipjack tuna fish farming was 3,028 tons/year and the result in 2014 was 460.82 tons, means that the skipjack tuna utilization was still under fishing. Meanwhile, the fishing attempt of 224 units was exceeding because it has passed the optimum limit of fishing by 102 units. The results of the study recommended several policies of the skipjack tuna management which are: (1) the amount limitations of the fish farming; (2) the management of the fishing attempts; and (3) the regulation of the fish farming closing season.Keywords: fisheries management, skipjack tuna (Katsuwonus pelamis), Prigi Fishing Port, TAC